2020
DOI: 10.37624/ijert/13.1.2020.12-27
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Blast-Loaded Steel and Reinforced Concrete Beam-to-Column Connections

Abstract: Resistance of steel and reinforced concrete (RC) beam-tocolumn connections to blast loading is presented in this paper. The steel and RC connections are analysed nonlinearly using the finite element (FE) software ABAQUS. Comparisons of the obtained results from the connections modelling with those of the experimental tests reveal the modelling accuracy. Then, the ETABS software is utilised to design 4 buildings including 2 steel buildings with 5 and 9 storeys and 2 RC buildings with the same number of storeys.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…At the same time, it was found that the temperature on the reinforcing rods reaches 853 °C, which is sufficient to ensure the fire resistance of R150 at the given calculated forces in the column, and the mosaic of movements along the Z axis was not significant and amounted to 1.1 mm. The maximum reinforcement area was 5.55 cm 2 . When ensuring R180 fire resistance at the given calculated forces in the column, the temperature at the corner reinforcing bars reached 914 °С and the program calculated additional reinforcement.…”
mentioning
confidence: 94%
“…At the same time, it was found that the temperature on the reinforcing rods reaches 853 °C, which is sufficient to ensure the fire resistance of R150 at the given calculated forces in the column, and the mosaic of movements along the Z axis was not significant and amounted to 1.1 mm. The maximum reinforcement area was 5.55 cm 2 . When ensuring R180 fire resistance at the given calculated forces in the column, the temperature at the corner reinforcing bars reached 914 °С and the program calculated additional reinforcement.…”
mentioning
confidence: 94%